Raymond Skyrme, Rubén Dario and the Pythagorean tradition. The University Presses of Florida, Gainesville, 1975; 107 pp. - Jrade, Cathy (El Colegio de México, 1977)
Se reseñó el libro: Rubén Dario and the Pythagorean tradition.